Neural indicators of misophonia related cognitive load - Tollefsrud, Michael A. (My University, 2025)
Misophonia is characterized by disproportionate emotional and physiological responses to specific “trigger” sounds, often accompanied by self-reported difficulty maintaining focus during exposure. This dissertation sought to provide objective evidence of such cognitive disruptions by combining behavioral measures of auditory working memory (WM) with electroencephalographic (EEG) indices of neural processing. Fifty-seven participants (27 misophonic, 30 control) completed a pitch-matching WM task under three distractor conditions: silence, neutral sounds, and individualized trigger sounds. EEG was analyzed using a time– frequency approach to assess changes in alpha (8–12 Hz) and theta (4–7 Hz) oscillatory activity during the retention interval. Behaviorally, misophonic participants exhibited reduced overall WM performance compared to controls and a selective decrease in response precision, without loss of accuracy, when exposed to trigger sounds, suggesting degraded memory fidelity under emotionally salient distraction. From the EEG analysis, misophonic participants showed lower frontal alpha and theta power across conditions, consistent with diminished inhibitory control and reduced cognitive control engagement, rather than trigger-specific effects. These results indicate that misophonia may involve a generalized attentional control vulnerability that amplifies the disruptive impact of emotionally salient auditory stimuli. Implications and directions for future research are discussed.
Keywords: Misophonia; Cognitive load; Working memory; Alpha band; EEG